EVALUASI IMPLEMENTASI PROGRAM PEMBELAJARAN IPA DALAM MEMFASILITASI LITERASI SAINS PADA PESERTA DIDIK SMP - Pardosi, Jenopa; Handoyo, Eko; Isnaeni, Wiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning in facilitating scientific literacy has not been optimally implemented in several junior high schools in Toba Regency. An evaluation of the science learning program is required to obtain an overview of the quality of program implementation as well as the scientific literacy profile of students. This study aims to analyze the quality of the implementation of the science learning program in facilitating scientific literacy and to identify students’ scientific literacy profiles. The study employed a mixed-methods approach, collecting qualitative and quantitative data through the application of the CIPP (Context, Input, Process, Product) evaluation model. The research was conducted at SMP Negeri 1 Lumban Julu and SMP Negeri 2 Lumban Julu. Data were collected using observation, interviews, questionnaires, and scientific literacy tests. Test data were analyzed using quantitative descriptive analysis techniques with the assistance of Microsoft Excel and Winstep software through Rasch modeling. Non-test data were analyzed using the Miles and Hubeman model. The results indicate that in both schools, the context and input components were categorized as complete, while the process component was categorized as good. In the product component, students’ scientific literacy achievement was in the moderate to high category across all indicators. Based on these findings, the implementation of the science learning program still needs to be improved, particularly in aspects that have not been optimally implemented, in order to enhance students’ scientific literacy.